A qualitative study exploring professional pharmacy services offered by community pharmacies in the state of Sarawak, Malaysia. Issue 3 (27th June 2017) - Kho, Boon Phiaw; Hassali, Mohamed Azmi; Lim, Ching Jou; Saleem, Fahad
Abstract: Objectives: The aim of this research is to obtain in-depth information on various aspects regarding the provision of professional pharmacy services by community pharmacies in Sarawak, Malaysia. Methods: Semi-structured interviews were conducted with a diverse group of community pharmacists selected via purposive and snowball sampling. The resultant interviews were audio-recorded, transcribed verbatim and analysed using thematic analysis. Key findings: In all, 20 community pharmacists took part in the study upon data saturation. Monitoring of health parameters, smoking cessation, weight management, medication review and disease state management were the extended pharmacy services provided. Service provision was influenced by respondents' intrinsic motivations, including having a desire to help others and achieving professional satisfaction. Practical and business considerations were other rationales for services provision. Intra-organisational barriers faced, including lack of time, personnel and physical space constrained services provision. Cultural issues, lack of committed customers, stock availability and price issues were extra-organisational challenges faced. The availability of market demands influenced respondents' plans for further service expansion. Conclusions: Community pharmacists have both noble intentions and commercial motivations to provide professional pharmacy services. However, various intra-organisational and extra-organisational barriers limit the variety of services provided by respondents. Demonstration of a more proactive attitude amongst pharmacists, as well as more opportunities for collaboration and strategic incentives by the government may be useful in encouraging them to expand the range of professional services. Consequently, the positive change will unlock their potential to improve the health and well-being of the general population.